2022
DOI: 10.1111/dth.15684
|View full text |Cite
|
Sign up to set email alerts
|

Vaccine‐induced erythrodermic psoriasis in a child successfully treated with secukinumab: A case report and brief literature review

Abstract: We report a case of a 7-year-old male patient with vaccine-induced erythrodermic psoriasis (EP) complicated by pulmonary infection, hypoproteinemia, and liver dysfunction successfully treated with secukinumab in combination with symptomatic and supportive therapy. The patient presented with diffuse flushing on the head, face, trunk, and limbs, which were covered with chaff-like white scales in the rashaffected area, with no blisters, pustules, and no apparent abnormalities in the palms, soles, nails, and joint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…83 Its use in the management of EP has been reported in several case series [27][28][29][30][31][32] and case reports. [33][34][35][36][37][38]84 However, there are no clinical trials available. The largest case series has been reported by Damiani et al who reported the results of a multi-center, international, retrospective, pilot study enrolling 13 EP patients receiving secukinumab for 52 weeks.…”
Section: Secukinumabmentioning
confidence: 99%
See 1 more Smart Citation
“…83 Its use in the management of EP has been reported in several case series [27][28][29][30][31][32] and case reports. [33][34][35][36][37][38]84 However, there are no clinical trials available. The largest case series has been reported by Damiani et al who reported the results of a multi-center, international, retrospective, pilot study enrolling 13 EP patients receiving secukinumab for 52 weeks.…”
Section: Secukinumabmentioning
confidence: 99%
“… 28 Of interest, two cases of pediatric EP successfully treated with secukinumab have been described. 37 , 38 …”
Section: Secukinumabmentioning
confidence: 99%
“…Psoriasis prevalence estimates on a global scale are being provided by an increasing number of populationbased research [32][33][34][35]. The prevalence of psoriasis varies around the globe.…”
Section: Introductionmentioning
confidence: 99%
“…1 EP following COVID-19 vaccination is more uncommon; Table I outlines reported cases. [3][4][5][6][7][8] Over one-half of these cases occurred following the Pfizer-BioNTech vaccine, one-half following the second dose, and three-fourths in males. The patient age ranged from 7 to 58 years old.…”
mentioning
confidence: 99%
“…1,3,8,9 Cases have been reported after non-mRNA COVID-19 vaccines; therefore, the mRNA component is likely not responsible. 7,8 Other vaccinations have also reportedly caused psoriasis flares, including influenza (H1N1), tetanus-diphtheria, BCG Q5 , and pneumococcal pneumonia. 1 Although this case adds to the literature on psoriasis flares following COVID-19 vaccination, such cases are uncommon.…”
mentioning
confidence: 99%